2006
DOI: 10.5194/nhess-6-451-2006
|View full text |Cite
|
Sign up to set email alerts
|

The mobility of Atlantic baric depressions leading to intense precipitation over Italy: a preliminary statistical analysis

Abstract: Abstract. The speed of Atlantic surface depressions, occurred during the autumn and winter seasons and that lead to intense precipitation over Italy from 1951 to 2000, was investigated. Italy was divided into 5 regions as documented in previous climatological studies (based on Principal Component Analysis). Intense precipitation events were selected on the basis of in situ rain gauge data and clustered according to the region that they hit. For each intense precipitation event we tried to identify an associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…In both EM and WM, results show that intensity of the circulation (depth of the cyclone, Laplacian, gradient and extension) and in some cases moisture content of the middle atmosphere play an important role in the characterization of C 90+98 (cyclones producing severe precipitation events) with respect to C 25 (cyclones producing mild precipitation events). Also, the speed of a cyclone center is an important characteristic explaining the severity of the precipitation event, though significant statistical evidence is not always present, as already shown by previous studies for Italy (Tartaglione et al, 2006) and the Alps (Frei and Shär, 2001). These links between synoptic patterns and precipitation represent a tool that can be applied to GCM results to associate changes of precipitation rainfall patterns to synoptic dynamics (Lionello and Giorgi, 2007) and to help diagnosing increases in hazardous intense precipitation events and drier conditions for the Mediterranean region.…”
mentioning
confidence: 77%
“…In both EM and WM, results show that intensity of the circulation (depth of the cyclone, Laplacian, gradient and extension) and in some cases moisture content of the middle atmosphere play an important role in the characterization of C 90+98 (cyclones producing severe precipitation events) with respect to C 25 (cyclones producing mild precipitation events). Also, the speed of a cyclone center is an important characteristic explaining the severity of the precipitation event, though significant statistical evidence is not always present, as already shown by previous studies for Italy (Tartaglione et al, 2006) and the Alps (Frei and Shär, 2001). These links between synoptic patterns and precipitation represent a tool that can be applied to GCM results to associate changes of precipitation rainfall patterns to synoptic dynamics (Lionello and Giorgi, 2007) and to help diagnosing increases in hazardous intense precipitation events and drier conditions for the Mediterranean region.…”
mentioning
confidence: 77%
“…[See, e.g., Brunetti et al (2002, Lucarini et al (2004Lucarini et al ( , 2006, Speranza et al (2006), Speranza and Tartaglione (2006), Tartaglione et al (2006), and the Mediterranean Experiment (MEDEX) phase 1 report (available at http://medex.inm.uib.es/) for related results and activities.] The study reported in Part I revealed, among other things, that diagnostics of extreme statistics can highlight interesting dynamical properties of the analyzed system.…”
Section: Introductionmentioning
confidence: 98%
“…Part I was originally motivated by the interest in weather having "major impact" (on human life and property) in the Mediterranean area, in particular intense precipitation and heat waves over Italy. See, for example, Brunetti et al (2002Brunetti et al ( , 2004; Lucarini et al (2004Lucarini et al ( , 2006b; ; Speranza and Tartaglione (2006); Tartaglione et al (2006) and the MEDEX Phase 1 report (available at http://medex.inm.uib.es/) for related results and activities. The study reported in Part I has revealed, among other things, that diagnostics of extreme statistics can highlight interesting dynamical properties of the analyzed system.…”
Section: Introductionmentioning
confidence: 99%
“…See, for example, Brunetti et al (2002Brunetti et al ( , 2004; Lucarini et al (2004Lucarini et al ( , 2006b); ; Speranza and Tartaglione (2006); Tartaglione et al (2006) and the MEDEX Phase 1 report (available at http://medex.inm.uib.es/) for related results and activities. The study reported in Part I has revealed, among other things, that diagnostics of extreme statistics can highlight interesting dynamical properties of the analyzed system.…”
Section: Introductionmentioning
confidence: 99%